Emerging Security Dynamics in Syria: Role of Foreign Powers - Mr. Sajid Aziz (CISS Insight Journal, 2016)
Syria currently presents a complex diplomatic, security and political mosaic. A country-wide truce, effected on 30 December, 2016 by Russia, Turkey and Iran, has ceased the war in considerable areas of Syria and brought in a modicum of fragile peace.1 This initiative has also been endorsed by both UN and USA. Though, the truce does not include areas controlled by Islamic State and Jabet Fateh al-Sham. Further talks between Syrian government forces and rebels groups took place in Astana, Kazakhstan, on 23 January 2017.2 These negotiations precede Geneva III talks, likely to be held in mid-February. Turkey’s Operation ‘Euphrates Shield’ has entered its fifth month.3 Militarily intervention in northern Syria on August 24, 2016, by Turkey purportedly is aimed at defeating and displacing ISIS from the Turkish border regions. Turkey along with Free Syrian Army (FSA) battled ISIS in Jarabulus and took its control and is currently waging a brutal war against it in al-Bab. But the equally important geopolitical rationale of Operation Euphrates Shield was to scuttle the vision of People’s Protection Units (YPG) to make the three Kurdish cantons of Jazira, Kobane and Afrin geographically contiguous. Moreover, USA and Syrian Democratic Forces (SMF), a coalition of Kurdish and Arab forces, have launched operation ‘Wrath of Euphrates’ against ISIS in Raqqa in the east of Syria.4 Taking advantage of Syrian government’s fight in the north and centre of Syria, ISIS took back the control of Palmyra from Syrian government and has again indulged in an orgy of demolishing treasured historical monuments and destroying artifacts. The recapturing of all of Aleppo gave a severe military and psychological blow to rebels.